Construction of a concept of sustainable residential college in Malaysian public universities - Buyung, Mohd Reduan; Shafii, Haryati; Buyung, Nurul Rezuana (Human Resource Management Academic Research Society, 2018)
This study is aimed at obtaining early information regarding the construction of a sustainable residential college. The problem of this study is the discomfort of living in residential colleges in Malaysian public universities. Discomfort affects the learning process of the occupants and affects the sustainability of residential colleges. The final impression of this offense leads to a deterioration in the quality of life. The research methodology is based on the literature review of residential colleges, Maslow's Theory of Needs, sustainable development, the influence of comfort and quality of life. The findings show that Maslow boelh's Theory of Needs is used as the basis for the provision of sustainable residential colleges, the concept of sustainable development as the basis for the concept of sustainable residential college and the comfort of the occupants affecting the quality of life as a whole. The future residential college should be developed on the basis of sustainability so residents can live comfortably and conducive thereby leading to improved quality of life.